The Role of Imum Mukim in Gampong Governance in Paya Bakong District of North Aceh Regency - Zulkifli Zulkifli; M Akmal; Muhammad bin Abubakar; Mulyadi Mulyadi (Malikussaleh Social and Political Reviews, 2021)
The purpose of this study is to explain how the role of Imum Mukim in Paya Bakong Sub-District in carrying out duties according to Law No. 11 of 2006 on The Government of Aceh and Qanun Aceh Number 04 of 2003 concerning Mukim government the Acehnese traditional governmental institution. It describes the Role of Imum Mukim in Gampong (Village) governance. The method used is descriptive qualitative. The data were collected through interviews, observations, literature studies, documentation, and field studies. The findings of the study showed that Mukim in Paya Bakong subdistrict has a role to play in the governance of Gampong but it has not been effectively carried out as stipulated in the Laws. The roles of Imum Mukim covers not only fostering people's lives in carrying out Islamic sharia, socialization of Islamic sharia, but also formulating policies concerning Gampong’s affaires. Withstanding that, theser role have not been carried out effectively, due to several reasons. Firstly, is the line of coordination between the Keuchik (Head of the Village) on the Gampong governance has not been authoriotatively imposed on the latter by the laws. For there is a sub district government that directly coordinated with the Keuchik based on Indonesian Governmental Laws. This has made the Mukim lost its political influence and implicitly implied that the Mukim is merely an accommodation of cultural valued, which is politically has no authority in the Gampong political and developmental affairs. Consequently, the Keuchik and its apparatus often left them uninform about the political and development of the Gampong.